A Rare Case of Moyamoya Disease in a 20-year-old Puerto Rican Female U.S. Soldier - Busey, Blake; Berry-Cabán, Cristobal S.; Hoedebecke, Kyle; Barts, Rachel N. (Puerto Rico Health Sciences Journal, 2014)
Moyamoya disease is a progressive, occlusive pathology involving the cerebral vasculature with particular involvement of the circle of Willis and its tributaries. The cause of moyamoya disease is unknown, but is believed to be hereditary. Females 20 to 39 years old with moyamoya represent 0.5% of all acute cerebral ischemia and infarcts with risk factors including smoking, estrogen-containing birth control use, coagulopathy, neoplasm, and congenital malformation. This case reports on a 20- year-old Puerto Rican female U.S. soldier with a 1-year history of migraine headaches with worsening right retro-orbital pain, blurred vision, and photophobia. The patient had minimal unilateral neurological deficits despite evidence of significant cerebral infarction on non-contrast computed tomography. Other neuroimaging findings were consistent with moyamoya disease with confirmation via cerebral angiography. This case details the process of diagnosis and treatment as well as discussing its incidence, identification, and treatment options.